Hemodynamics of Proximal Coronary Lesions in Patients Undergoing Transcatheter Aortic Valve Implantation: Patient-Specific In Silico Study - Yahia Bellouche; Sirine Abdelli; Sinda Hannachi; Clement Benic; Florent Le Ven; Romain Didier (Bioengineering)
Aortic stenosis (AS) frequently coexists with coronary artery disease (CAD), complicating revascularization decisions. The use of coronary physiology indices, such as the fractional flow reserve (FFR), instantaneous wave-free ratio (iFR), and coronary flow reserve (CFR), in AS patients remains debated, particularly after transcatheter aortic valve implantation (TAVI). In this study, we employ computational fluid dynamics (CFD) to evaluate coronary hemodynamics and assess changes in the wall shear stress (WSS) before and after TAVI. Our analysis demonstrates strong agreement between CFD-derived and invasive FFR measurements, confirming CFD’s reliability as a non-invasive tool for coronary physiology assessment. Furthermore, our results show no significant changes in FFR (<semantics>p=0.92</semantics>), iFR (<semantics>p=0.67</semantics>), or CFR (<semantics>p=0.34</semantics>) post-TAVI, suggesting that these indices remain stable following aortic valve intervention. However, a significant reduction in high WSS exposure (59% to 40.8%, <semantics>p<0.001</semantics>) and the oscillatory shear index (OSI: 0.32 to 0.21, <semantics>p<0.001</semantics>) was observed, indicating improved hemodynamic stability. These findings suggest that coronary physiology indices remain reliable for revascularization guidance post-TAVI and highlight a potential beneficial effect of aortic stenosis treatment on plaque shear stress dynamics. Our study underscores the clinical utility of CFD modeling in CAD management, paving the way for further research into its prognostic implications.